Impact of Climate Change on Wheat Production in Dinajpur Region of Bangladesh: an Econometric Analysis - Syeda, JA (Journal of Environmental Science and Natural Resources, 2018)
Dinajpur is the highest wheat producing northern district in Bangladesh and wheat is the second most essential cereal crop after rice in this country. This is much sensitive to climatic change. The main concern of this paper was to quantify the long-term effect of climate change on wheat production in Dinajpur district using multiple regression analysis technique taking several climatic variables for 1948-2004. The approximately significant effects were found for the climatic variables of average minimum temperature (tmn), average dry bulb temperature (td) and total rainfall (ttr) on wheat production. It may be reported that one percent increase in tmn increases the yield rate by about 2.62%, one percent increase in td decreases the yield rate by about 2.58% and one percent increase in ttr increases the yield rate by about 0.03%. J. Environ. Sci. & Natural Resources, 10(2): 157-162 2017